(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
This study is titled Financing Federal Universities in South East Zone Nigeria: Implication for Global Competiveness. The study has two objectives among which are; to find out the provision of finance to Federal Universities in South East Zone, Nigeria and its implication for global competiveness and to determine the level of utilization of finance in federal universities in South East Zone, Nigeria and its implication for global competiveness. In line with these objectives, two research questions, two null hypotheses will be asked and formulated respectively. Related literature was reviewed; concepts such as financing, provision of funds, utilization of funds, global competiveness will be discussed. In addition, the review will be on the provision of finance to Federal Universities in South East Zone, Nigeria and its implication for global competiveness and the level of utilization of finance in Federal Universities in South East Zone, Nigeria and its implication for global competiveness. Descriptive research design will adopted for the study. A total of 365 respondents will be sampled from the total population of 7500, through the use of research advisor (2006). A structured questionnaire will be used to collect data from the respondents. Descriptive statistics will be used to analyze the bio- data of the respondents. The data collected will be presented in tables and analyzed using weighted means to give the responses of respondents to the research questions. The two null hypotheses will be tested using One Way Analysis of Variance (ANOVA) at 0.05 alpha level of significance. The findings of the study are: there is inadequate funding of federal universities in south east zone which affects there ability to compete favourably with other universities globally and that the finding shows that the fund made available to federal universities were not judiciously utilized, this also affect their ability to compete globally. It was recommended that Federal government of Nigeria should as a matter of importance deploy the needed fund for the management of federal universities in south east zone and that the fund made available to federal universities should be utilized judiciously in order enhance healthy competition globally